Velocity and attenuation analysis methods for characterizing the properties of wheat flour noodle dough. Issue 4 (10th May 2019) - Strybulevych, Anatoliy; Diep, Sally; Daugelaite, Daiva; Guillermic, Reine‐Marie; Page, John H.; Hatcher, David W.; Scanlon, Martin G.
Abstract: Background and objectives: Noodles are a traditional staple of the Asian diet, and ensuring quality during production is important for both producers and consumers. Ultrasound is sensitive to the mechanical properties of dough that relate to product texture and is therefore a promising quality assessment tool. For optimal results, it is important to assess the merits of different ultrasonic analysis methods. Findings: Mechanical properties of raw Asian noodle dough made from two red spring wheat varieties were measured by a low‐frequency ultrasonic transmission technique. Entire transmitted ultrasonic pulses, having passed through disks of the noodle dough, were analyzed using fast Fourier transform (FFT) techniques, enabling the transmitted phase and amplitude as a function of frequency to be compared for samples of different thickness. This approach allows noodles made from different wheat varieties to be discriminated through ultrasonic velocity and attenuation measurements. Conclusions: The frequency dependence of both velocity and attenuation coefficient, which was revealed the FFT method, points to the presence of gas bubbles, which even in small amounts can influence texture and hence noodle quality. Significance and novelty: In addition to providing insights on properties that influence noodle quality, the frequency dependence of velocity and attenuation found by the FFT analysis can explain differences reported by different analysis techniques.